Improving Clean and Healthy Living Behaviors Among Indonesian Migrant Workers in Malaysia - Widya Hary Cahyati; Ratna Dewi Kusumaningtyas; Wandah Wibawanto; Annisa Putri Salsabila; Regina Marsha Nathaniela; Sultan Aulia Rahmat (Universitas Negeri Semarang, 2024)
The Clean and Healthy Living Behavior Program (PHBS) is an effort to prevent disease by getting used to clean living and healthy behavior. PHBS is very important to be applied to the entire community, including Indonesian Migrant Workers (PMI). PMI live overseas, so health is very important. If they get sick, it will create new problems because access to health services is limited, and there is no family who can look after them. The solution offered to partners' problems is socialization regarding clean and healthy living habits, as well as how to get used to clean and healthy behavior. The development of a video about how to get used to living a clean and healthy life aims to increase the capacity of Indonesian migrant workers in Malaysia to get used to living a clean and healthy life, so that they can prevent disease attacks. The use of videos is intended to make socialization activities more effective. The Indonesian Embassy in Johor Bahru is a service partner, which will assist in bridging the service program that UNNES will carry out for PMI in the Johor Bahru Region. After conducting outreach to PMIs, the next step is to form several groups consisting of several PMIs to ensure the sustainability of the implementation of the PHBS program. The result of this activity is the availability of the PMI group as a forum for sharing and doing joint activities , as well as increasing knowledge and understanding about PHBS.